1994
DOI: 10.21273/jashs.119.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Transformation of Peach Tissues by Particle Bombardment

Abstract: Physical and biological parameters affecting the efficiency of biolistic transformation of peach were optimized using ß-glucuronidase (GUS) as a reporter gene, such that efficiency of transient GUS expression in peach embryo-derived callus was increased markedly. Transient expression was also obtained in embryonic axes, immature embryos, cotyledons, shoot tips, and leaves of peach. Stable expression of a fusion gene combining neomycin phosphotransferase (NPTII) and ß-glucuronidase activities has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 41 publications
2
15
0
2
Order By: Relevance
“…Development of genotype-independent transformation procedures will be very difficult to achieve with current technology. Different authors have tried unsuccessfully to transform meristems from micropropagated shoot tips (Ye et al, 1994;Druart et al, 1998). Meristem transformation may eliminate the need for regeneration in production of transgenic plants, allowing genetic manipulation of established cultivars.…”
Section: Shortcomings In the Transformation Of Fruit Treesmentioning
confidence: 99%
“…Development of genotype-independent transformation procedures will be very difficult to achieve with current technology. Different authors have tried unsuccessfully to transform meristems from micropropagated shoot tips (Ye et al, 1994;Druart et al, 1998). Meristem transformation may eliminate the need for regeneration in production of transgenic plants, allowing genetic manipulation of established cultivars.…”
Section: Shortcomings In the Transformation Of Fruit Treesmentioning
confidence: 99%
“…In this species shoots have been regenerated with high efficiency from in vitro propagated leaves , mature cotyledon (Pooler and Scorza, 1995), immature cotyledon (Mante et al, 1989) and immature zygotic embryos (Hammerschlag et al, 1985). High efficiency of peach bombardment with desired transgenes is also elaborated (Ye et al, 1994), but there are no transformed plants yet. Similar situation, despite of three elaborated regeneration systems, was described by Ainsley et al (2001) for paper shell almond.…”
Section: Agrobacterium Mediated Transformationmentioning
confidence: 99%
“…In terms of transformation, Scorza et al (1990b) reported Agrobacterium-mediated transformation of peach explants including leaf segments, immature embryos, and embryogenic callus. Ye et al (1994) demonstrated the feasibility of obtaining stable transgenic peach embryo callus tissue by biolistic transformation but no transgenic shoots were developed from this callus. There are only two reports of stable transgenic peach plant production.…”
Section: Introductionmentioning
confidence: 99%